Water Management Plant Information System - Lim Kean Wei,; Prof. Madya Dr. Shahreen Binti Kasim, (Applied Information Technology And Computer Science, 2023)
Due to the poor water management issue faced by Sawit Kinabalu Sdn Bhd, a proposed water management system was requested to be developed in this project to overcome the challenges such as inefficient working performance. The proposed system should be accessible by the personnel of Sawit Kinabalu Sdn Bhd and it can manage the data of operating units and water management. The method used to develop the system is agile scrum methodology by using the Laravel framework. Laravel is a PHP-based framework used to develop large-scale application systems. The proposed system is expected to help the clients by lowering workflow complexity, which also increases the productivity and efficiency of the water management workflow. For future enhancement, it is expected to be integrated with IOT technical devices to record and manage the data systematically and automatically.